PENERAPAN TEKNIK PURSED LIPS BREATHING DAN POSISI SEMI FOWLER TERHADAP NILAI RESPIRATORY RATE PADA PASIEN TUBERCULOSIS PARU DI RUANG WIJAYA KUSUMA RSUD OTO ISKANDAR DINATA SOREANG - Okhvi, Ririn Antya (JURNAL KESEHATAN KARTIKA, 2024)
Background: The Global Tuberculosis Report 2022 reported that Tuberculosis cases in Indonesia reached 969,000 cases, an increase of 17% since 2020 which amounted to 824,000 cases. Tuberculosis is a contagious infectious disease caused by Mycobacterium tuberculosis. Symptoms that generally appear prolonged are shortness of breath which causes an increase in the frequency of breathing in patients. Pursed Lips Breathing is a non-pharmacological measure that can be applied to reduce shortness of breath, increase alveolus development so that pressure increases and induce normal breathing patterns. In addition, applying the semi-fowler position in patients with TB can help lung development and reduce pressure from the visceral-visceral abdomen on the diaphragm so that it can be lifted and the lungs will expand maximally and the volume of the lungs will not be fulfilled, therefore shortness of breath will decrease. Objective: was to determine the application of pursed lips breathing exercise techniques and semi-fowler position to the value of respiratory rate in pulmonary TB patients in X Hospital. Methods: descriptive research using a case report research design in the form of nursing care. Data collection methods in this study used interviews, observation, and physical examination techniques. Results: this study showed that the respiratory rate decreased after practicing the pursed lips breathing technique and semi-fowler position for 3 days with a respiratory rate of 26 x/min to 18 x/min. Conclusion: pursed lips breathing technique and semi-fowler position can reduce respiratory rate values in patients with shortness of breath.